2015
DOI: 10.3171/2014.10.jns142264
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of adverse radiation effects following Gamma Knife radiosurgery for arteriovenous malformations

Abstract: OBJECT The authors review outcomes following Gamma Knife radiosurgery (GKRS) of cerebral arteriovenous malformations (AVMs) and their correlation to postradiosurgery adverse radiation effects (AREs). METHODS From a prospective institutional review board–approved database, the authors identified patients with a minimum of 2 years of follow-up and thin-slice T2-weighted MRI sequences for volumetric analysis. A total of 105 AVM patients were included. The authors analyzed the incidence and quantitative changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Radiationinduced changes typically develop 12-18 months post-SRS and, unless symptomatic or permanent, bear little clinical significance except to herald future obliteration. 1 A higher margin dose was previously reported to be a key predictor of obliteration, 1,3,6,10,22,30,38 which was not demonstrated in this cohort. In the present report of AVM patients, all of whom had obliteration, we found that those who received a margin dose > 24 Gy responded sooner.…”
Section: Predictors Of Early Avm Obliterationmentioning
confidence: 56%
See 2 more Smart Citations
“…Radiationinduced changes typically develop 12-18 months post-SRS and, unless symptomatic or permanent, bear little clinical significance except to herald future obliteration. 1 A higher margin dose was previously reported to be a key predictor of obliteration, 1,3,6,10,22,30,38 which was not demonstrated in this cohort. In the present report of AVM patients, all of whom had obliteration, we found that those who received a margin dose > 24 Gy responded sooner.…”
Section: Predictors Of Early Avm Obliterationmentioning
confidence: 56%
“…Arteriovenous malformations continue to represent a significant clinical challenge, and expert opinions differ regarding their optimal management. 1 Treatment goals can vary among patients: reducing seizure activity, ameliorating symptomatic chronic "vascular steal," or alleviating neurological deficits caused by associated cerebral edema. However, the main goal of any intervention for AVMs remains complete obliteration of the nidus, thereby eliminating subsequent risk of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse radiation effects have been associated with a large nidus and a higher margin dose, among other factors. 5,14 Historically, the volume-staging strategy emerged to enable the administration of a higher global dose to a large volume while maintaining a low rate of adverse effects. 23 With the exception of Dalyai et al 6 , we administered a higher margin dose than the vast majority of reported series for volumestaged fractionation of large cerebral AVMs (20 Gy at the 50% isodose), and we used a longer time interval between stages.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a significant challenge in image registration for open craniotomies. However, once resolved, this methodology will provide an objective means of comparing parameters can affect how physicians utilize stereotactic radiosurgery in treatment of brain tumors, 87,88 arterio-venous malformations, 89 and cavernous malformations 90 by augmenting current understanding of treatment related MR changes.…”
Section: Image Acquisitionmentioning
confidence: 99%